PENGARUH PROBLEM BASED LEARNING (PBL) MELALUI PENDEKATAN METAKOGNITIF BERBANTUAN JURNAL BELAJAR EKOSISTEM TERHADAP KEMAMPUAN PEMECAHAN MASALAH - Romadhan, Siddik; Fajarianingtyas, Dyah Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the effect of PBL through a metacognitive approach using an ecosystem learning journal on problem-solving abilities. The research method used a quantitative research type of quasi experiment. Data analysis used a free sample t test. The research subjects were 30 fifth grade students. The research location was at SDN Kalianget Timur X. Based on the results of the study, it was known that there was an effect of PBL assisted by an ecosystem learning journal. This shows that the problem-solving abilities of students taught using PBL assisted by an ecosystem learning journal increased by 76%.